Measurement of the Λ0b, Ξ−b, and Ω−b baryon masses - Aaij, Roel; Adametz, Aleksandra; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; et al. (Physical review letters, 2013)
Bottom baryons decaying to a J/ψ meson and a hyperon are reconstructed using 1.0 fb−1 of data collected in 2011 with the LHCb detector. Significant Λ0b→J/ψΛ, Ξ−b→J/ψΞ− and Ω−b→J/ψΩ− signals are observed and the corresponding masses are measured to be M(Λ0b)=5619.53±0.13(stat.)±0.45(syst.) MeV/c2, M(Ξ−b)=5795.8±0.9(stat.)±0.4(syst.) MeV/c2, M(Ω−b)=6046.0±2.2(stat.)±0.5(syst.) MeV/c2, while the differences with respect to the Λ0b mass are M(Ξ−b)−M(Λ0b)=176.2±0.9(stat.)±0.1(syst.) MeV/c2, M(Ω−b)−M(Λ0b)=426.4±2.2(stat.)±0.4(syst.) MeV/c2. These are the most precise mass measurements of the Λ0b, Ξ−b and Ω−b baryons to date. Averaging the above Λ0b mass measurement with that published by LHCb using 35 pb−1 of data collected in 2010 yields M(Λ0b)=5619.44±0.13(stat.)±0.38(syst.) MeV/c2.
Im Titel sind "0" und "-" hochgestellt und "b" jeweils tiefgestellt
LHCb Collaboration: R. Aaij, A. Adametz, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere
Gesehen am 23.03.2021